Pengaruh Harga, Kualitas Pelayanan Dan Lokasi Terhadap Keputusan Pembelian Pada Konsumen Alfamart - I Ketut Sudarnaya; I Made Sukadana (ARTHA SATYA DHARMA, 2022)
This research aims to find out the Effect of Price, Service Quality and Location on Purchasing Decisions in Alfamart Consumers (Case Study at Alfamart Raya Sangsit). This research uses quantitative approach methods. The number of samples used in this study was 99 respondents. The analytical techniques used in this study are Validity and Reliability Test, Multiple Linear Regression Analysis, Classical Assumption Test, Determination Analysis Model Test, and F-Test and Hypothesis Test with T-Test. The results of the purchase decision on Alfamart Raya Sangsit consumers by 84.6% and 15.4% were influenced by other factors not studied in the study. Therefore, the company needs to pay attention to the variables that affect consumer purchasing decisions so that it can be used as a study in strategic decision making in increasing sales volume.